Lactylation in urological malignancies: emerging mechanisms and therapeutic direction - Lin, Jiafeng; Yuan, Chenye; Liu, Chunsheng; Zhang, Minjie; Luo, Jianbin; Wu, Zhihuang; Ma, Qinghong; Xie, Shengbiao; Liang, Yufeng; Chen, Guoqiang (Frontiers in Cell and Developmental Biology, 2026)
Urological malignancies represent a group of highly aggressive tumors with a strong tendency toward therapy resistance. Their pathogenesis is closely associated with metabolic reprogramming and epigenetic regulation. In recent years, lactylation, a novel form of post-translational modification, has garnered significant attention due to its crucial role in linking cellular metabolism with epigenetics. By covalently modifying lysine residues on both histone and non-histone proteins, lactylation dynamically regulates gene transcription and protein function, thereby influencing malignant behaviors in urological malignancies—including proliferation, metastasis, immune evasion, and therapeutic resistance. This review begins by systematically outlining the fundamental characteristics of lactylation and its regulatory networks. It then summarizes the general roles of lactylation in cancer, with a particular emphasis on its mechanisms and functional implications in urological malignancies. Finally, we discuss current research challenges and future directions, aiming to provide new insights into the metabolic–epigenetic interplay in urological malignancies and to establish a theoretical foundation for targeting lactylation as a potential therapeutic strategy and prognostic biomarker.